Measurement of thermal and carrier transport properties of si using transmission photoacoustic techniques / Chan Kok Sheng …[et al.] - Chan, Kok Sheng; Mat Yunus, W. Mahmood; Wan Yunus, Wan Md. Zin; Talib, Zainal Abidin; Kassim, Anuar (2006)
The photoacoustic detection technique heat transmission configurations was utilized to study the thermal and carrier transport properties of boron-doped silicon wafer. The photoacoustic amplitude and phase signals were measured as a function of the optical beam modulation frequency as well as optical beam power. The measurements were performed in an enclosed photoacoustic cell at room temperature. The experimental results shown that in the thermally thick modulation-frequency region, the photoacoustic signal amplitude can single out the heating source responsible for the photoacoustic signal. The thermal diffusivity value and transport parameters (diffusion coefficient, surface recombination velocity, and carrier recombination lifetime) were determined by fitting the experimental photoacoustic phase data to the theoretical model. The present investigation shows a significant step towards demonstrating the use of the photoacoustic technique to perform the quantitative characterization of semiconductor materials.